Quality and dose optimization in canine chest radiography using a digital radiography system - Souza, Sérgio Augusto Santana de [UNESP]; Alves, Allan Felipe Fattori [UNESP]; Locci Nogueira dos Santos, Alexandre [UNESP]; Alves de Oliveira, Abner [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Pina, Diana Rodrigues [UNESP] (Elsevier, 2022)
Radiography is becoming increasingly popular as a diagnostic tool in veterinary radiology services. During radiological procedures, containment of the animal is often necessary to ensure a safe examination. This work aimed to establish a methodology to optimize canine radiography protocols in canines of different sizes. Here, was used a set of four homogeneous canine chest phantoms with two different views: dorsoventral and lateral. The authors developed this set of homogeneous canine chest phantoms previously. Effective detective quantum efficiency and entrance skin dose for each test technique was estimated. Then, all test techniques were applied to canine subjects. This allowed subjective evaluations through visual grading analysis (VGA), by the veterinary radiologists. The VGA chooses which test techniques include relevant structures to ensure a medical diagnosis, selecting them as optimized techniques. Based on the ALARA (As Low As Reasonably Achievable) principle, a set of gold standard techniques was chosen among all optimized techniques. Physical parameters were used to identify the image quality of the gold standard for all sizes of patients (small-S, medium-M, large-L, and Giant-G). This work presented a new methodology to optimize digital radiography in veterinary procedures. This optimization process provides a better risk-benefit ratio for professionals and animal owners and a better cost-benefit ratio for radiology services. This work can be performed on any radiological equipment or other anatomical structures.
Keywords: Canine phantom; Digital radiology; Dose; Veterinary medicine